Manajemen Pembinaan Nazir Wakaf Studi di Perwakilan Badan Wakaf Indonesia Provinsi Sumatera Barat - Firdaus, Rahmat (ITB AAS INDONESIA Surakarta, 2024)
Abstract: This research aims to determine the management of waqf nazir development at the Indonesian Waqf Representative Body, West Sumatra Province. This research is descriptive qualitative in nature using observation, interview and documentation data collection techniques. Data analysis was carried out using the stages of data reduction, display and conclusion. The results of this research show that the management of waqf nazir coaching involves several forms of programs, first, KISWA (Study of current issues regarding waqf), second, Coaching Session, third, SITAWA (Literacy and Questions and Answers about Waqf, fourth, (Sharing Experiences between Nazhir) the aim of this program is to increase nazir's knowledge in managing and developing waqf assets. Fifth, the waqf nazir competency certification program. This program aims to make nazir professionals in developing waqf assets Keywords: Waqf nazir development, Indonesian Waqf Board